Binding of double-stranded DNA by Escherichia coli RecA protein monitored by a fluorescent dye displacement assay. - Zaitsev, E N (1998)
We have developed a new assay to characterize the double-stranded DNA (dsDNA) binding properties of RecA protein. This assay is based on measurement of changes in the fluorescence of a 4',6-diamidino-2-phenylindole (DAPI)-dsDNA complex upon RecA protein binding. The binding of RecA protein to a complex of DAPI and dsDNA results in displacement of the bound DAPI, producing a decrease in the observed fluorescence. DAPI displacement is dependent on both RecA protein and ATP; dATP and, to a lesser extent, UTP and dCTP also support the DAPI displacement reaction, but dGTP, GTP, dITP and TTP do not. Binding stoichiometry for the RecA protein-dsDNA complex measured by DAPI displacement is 3 bp per RecA protein monomer in the presence of ATP. These results, taken together with data for mutant RecA proteins, suggest that this DAPI displacement assay monitors formation of the high affinity DNA binding state of RecA protein. Since this state of RecA protein defines the form of the nucleoprotein filament that is active in DNA strand exchange, these findings raise the possibility that the RecA protein-dsDNA filament may possess a homologous pairing capacity.